Die casting - Cook, Jerome T.; Vaccari, John A. (Dearborn, Mich.: Society Manufacturing Engineers, 2003)
To better understand the versatility of die casting, this program explores in detail: The hot-chamber machine process, The cold-chamber machine process, Die casting tooling and The common die cast metals & their various properties.
Keywords: Die-casting; Dies (Metal-working)